The Power Of Satisfaction And Trust: Unlocking E-WOM's Influence On Consumer Repurchase Intentions In Digital Marketplaces - Shahrial Putra, Defin; Wicaksono, Teguh; Abdurrahim, Abdurrahim (Publisher Cv. Inara, 2024)
The purpose of this research is to investigate how consumer repurchase intention in the setting of e-commerce is impacted by electronic word of mouth (e-WOM), trust, and customer happiness. The demographic of this study is the people who live in the North Banjarmasin District, and the research sample consists of 399 respondents who buy at the marketplace. The study used a quantitative design. An analysis method called structural equation modeling (SEM) is applied. The findings of the study demonstrate the significance of these variables in influencing the intention to repurchase, and eWOM is recognized as a key tactic for encouraging customers to share pleasant experiences with one another. However, e-WOM is negatively impacted by the possibility of disseminating false information. According to research, e-WOM, trust, and customer happiness all significantly influence the desire to repurchase. Reliability of work, completeness of information, and timeliness of delivery can all be used to gauge this level of confidence